Dimensions of Sustainable Tour Experiences. Issue 5 (3rd September 2021) - Brochado, Ana; Souto, Jenny; Brochado, Fernando
ABSTRACT: Tour operators are crucial to supply chain management within sustainable tourism. This research sought to identify sustainable tour dimensions from the tourists' perspective. The sample comprised 878 post-experience online reviews of 20 tours across Portugal, written by tourists from different countries. Mixed content analysis methods (i.e., qualitative narrative and quantitative computer-assisted analyses) produced results used to generate a concept map of 12 themes: tour, guide, experience, hike, service, food, recommendation, fun, return, walk, difference, and wildlife. Each theme contains concepts related to service quality and experience dimensions. The findings provide a better understanding of how tourists perceive sustainable tour experiences.